Case report: De novo variant of SETD1A causes infantile epileptic spasms syndrome - Lan, Mingping; Wang, Yanjuan; Li, Sixiu; Zhao, Lili; Liu, Ping; Hu, Wenguang (Frontiers in Neurology, 2023)
Infantile epileptic spasms syndrome (IESS) is one of the most common epileptic encephalopathy encephalopathies in of infancy, with the typical clinical features defined by of a triad of epileptic spasms, hypsarrhythmia, and developmental delay. Genetic factors are important causes of IESS, .The SETD1A (SET Domain Containing 1A) gene encodes a histone lysine methyltransferase that leads to the activation activates of gene transcription signaling through histone H3 lysine K4 H3K4 methylation. Mutations in the SETD1A gene have previously been reported to be associated with schizophrenia, and some have been reported to cause seizures. Herein, we report a case of IESS caused by a SETD1A gene mutation. Video electroencephalogram electroencephalography(VEEG) showed hypsarrhythmia, . No specific findings were obtained and after brain MRI and and metabolic work-up showed no specific findings. The seizures disappeared after treatment with adrenocorticotropic hormoneACTH, vitamin B6, and valproic acid during hospitalization. Genetic testing revealed that the child had a c.3005_3006 del (p.Glu1002Glyfs*20) variant (NM_014712.3:c.3005_3006 delAG, p.Glu1002Glyfs*20) in the exon 12 of the SETD1A gene, representing . This variant is a de novo mutation. There has been no previous report on the SETD1A gene causing infantile spasms. At the same time, wWe also summarize the existing literature on SETD1A gene-related epilepsy , as to provide a reference for clinical diagnosis and treatment.